HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN KESEJAHTERAAN PSIKOLOGIS MAHASISWA - Ade Maharani; Lisa Putriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early adulthood is a crucial developmental stage characterized by complex academic, social, and personal demands that can impact students’ psychological well-being. This study aims to determine the relationship between peer social support and students’s psychological well-being. The study used a quantitative approach with a correlational design with a population of 2.856 students from the Faculty of Education, Universitas Negeri Padang (FIP UNP), entering in 2023 and 2024. The study sample consisted of 351 students selected using the Slovin formula with proportional random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed descriptively using Microsoft Excel and correlational analysis with SPSS. The result showed that peer social support and students’ psychological well-being were in the high category. The correlation analysis showed a positive and significant relationship between the two variables (r=0,291; p>0,05). This finding confirms that the higher the peer social support, the higher the students’ psychological well-being. Therefore, strengthening peer support programs in higher education needs to be optimized to support students’ mental health.